Changes on the soft tissues of the oral cavity during the orthodontic treatment depending on the type of orthodontic appliance - Arapović-Savić Marijana; Umićević-Davidović Mirjana; Arbutina Adriana; Obradović Marija; Đukić Igor (Scripta Medica, 2016)
Introduction : Periodontal status and malocclusions are closely related. Retention places that enable for detention of food caused by various malocclusions, make selfcleaning and proper hygiene difficult and as such endanger the integrity of the soft tissues. Correctly applied orthodontic treatment has positive effects on periodontal tissues as it reduces the risk of damage and inflammations. One of the key factors for successful orthodontic therapy is adequate maintaining of the oral hygiene, which includes removal of dental plaque, the main cause of deterioration of the soft tissues of the oral cavity. Aim of the study: Establish the connection between changes in the soft tissues of the oral cavity and the type of used orthodontic appliance. Establish the time interval for appearance of changes on the soft tissues of the oral cavity. Patients and Methods: This research included 120 patients who were divided into three groups depending on the type of the orthodontic appliance used (mobile orthodontic appliance - active, mobile orthodontic appliances - functional and fixed orthodontic appliances). Examinations were performed three times: at the beginning of the treatment, after three months of therapy and after six months of therapy. In order to analyze the status of the soft tissues of the oral cavity and level of hygiene we used: Silness-Loe plaque index and Loe-Silness gingival index. Results: In patients divided by the type of orthodontic therapy, a statistically significant difference in the value of indexes after three and six months of wearing orthodontic appliances was found in patients who wore fixed orthodontic appliances. There was a difference in increased index values among this group when compared to subjects treated with mobile orthodontic appliances. Conclusion: During the orthodontic therapy, especially with fixed orthodontic appliances, patients must pay attention to adequate oral hygiene maintenance in order to avoid any unwanted changes on soft tissues of the oral cavity.